2020
DOI: 10.13057/biodiv/d211011
|View full text |Cite
|
Sign up to set email alerts
|

Response of parasitoids to invasive pest Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae) on cassava crop in Bali, Indonesia

Abstract: Abstract. Supartha IW, Yudha IKW, Wiradana PA, Susila IW. 2020. Response of parasitoids to invasive pest Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae) on cassava crop in Bali, Indonesia. Biodiversitas 21: 4543-4549. Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae) is an invasive pest that entered Indonesia in 2010 and attacks cassava plants, especially in Bali Province. This study aimed to identify species and establish the population distribution mapping, community structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…This study used a survey method with a sample location determined purposively [14,15] at three altitudes, namely <500; 500-1,000; >1,000 m.a.s.l. While the determination of the sample unit was using the diagonal method (Figure 1).…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…This study used a survey method with a sample location determined purposively [14,15] at three altitudes, namely <500; 500-1,000; >1,000 m.a.s.l. While the determination of the sample unit was using the diagonal method (Figure 1).…”
Section: Samplingmentioning
confidence: 99%
“…FAW spreads as random in the field, following the spread of the host plant [23]. Insects' abilities to locate food, escape predators, and perhaps be moved away by the wind are influencing the dispersal pattern [14]. According to Du Plessis et al [24], ambient temperature plays an essential impact in the FAW invasion process, particularly the adverse environmental aspects for its growth phase.…”
Section: Distribution Of Faw On Maize Crop In Karo Regencymentioning
confidence: 99%
“…Meanwhile, young plant leaves have much softer tissue-making cells so that insect larvae prefer them (Badenes-Perez et al 2014;Bhusal and Bhattarai 2019). In addition, young leaves usually contain more water (succulent), so it is very popular with phytophage insects (Supartha et al 2020).…”
Section: The Range Of the Number Of Maize Leaves Attacked By S Frugiperda Larvae Per Plantmentioning
confidence: 99%
“…The results showed that FAW that spread evenly throughout districts/cities in Bali has a random distribution pattern (S 2 /X=1). The pattern of spread is caused by the urge to find food, avoid predators, influence the climate, and get carried away by the wind (Supartha et al 2020).…”
Section: Distribution Of S Frugiperda In Balimentioning
confidence: 99%
“…F. arisanus was not found in Jembrana, whereas A. japonica was only found in Badung, Bangli, Gianyar, and Klungkung as shown in Figure 4. In addition, several factors influence parasitoid distribution, including biotic and abiotic factors (Supartha et al 2020;Yudha et al 2020).…”
Section: Distribution Of S Adipata Parasitoids In Balimentioning
confidence: 99%